The adverse impact of microplastics and their attached pathogen on hemocyte function and antioxidative response in the mussel Mytilus galloprovincialis. (June 2023) - Sun, Chaofan; Teng, Jia; Wang, Dongyu; Zhao, Jianmin; Shan, Encui; Wang, Qing
Abstract: Microplastics (MPs) are widely distributed in marine environments, and they are easily attached by various microorganisms, including pathogenic bacteria. When bivalves mistakenly eat MPs, pathogenic bacteria attached to MPs enter their bodies through the Trojan horse effect, causing adverse effects. In this study, the mussel Mytilus galloprovincialis was exposed to aged polymethylmethacrylate MPs (PMMA-MPs, 20 μm) and Vibrio parahaemolyticus attached to PMMA-MPs to explore the effect of synergistic exposure by measuring lysosomal membrane stability, ROS content, phagocytosis, apoptosis in hemocytes, antioxidative enzyme activities and apoptosis-related gene expression in gills and digestive glands. The results showed that MP exposure alone did not cause significant oxidative stress in mussels, but after long-term coexposure to MPs and V. parahaemolyticus, the activities of antioxidant enzymes were significantly inhibited in the gills of mussels. Both single MP exposure and coexposure will affect hemocyte function. Coexposure can induce hemocytes to produce higher ROS, improve phagocytosis, significantly reduce the stability of the lysosome membrane, and induce the expression of apoptosis-related genes, causing apoptosis of hemocytes compared with single MP exposure. Our results demonstrate that MPs attached to pathogenic bacteria have stronger toxic effects on mussels, which also suggests that MPs with pathogenic bacteria might have an influence on the immune system and cause disease in mollusks. Thus, MPs may mediate the transmission of pathogens in marine environments, posing a threat to marine animals and human health. This study provides a scientific basis for the ecological risk assessment of MP pollution in marine environments. Graphical abstract: Image 1 Highlights: Function of hemocytes was disrupted by PMMA-MPs attached with pathogen in mussel. The PMMA-MPs attached with pathogen causes obvious oxidative stress in gills. The MPs attached with pathogen caused more toxic effects to mussel than single MPs. MPs can act as vectors to promote pathogen transfer and cause damage to mussel.